The impact of climate change on the small island developing states of the Caribbean - Maharaj, S; Shobha S. Maharaj (2011)
Small Island Developing States (SIDS) of the Caribbean are one of the world’s ‘hottest’ ‘biodiversity hotspots’. However, this biodiversity continues to be threatened by habitat loss, and now, by climate change. The research reported here investigated the potential of species distribution modelling (SDM) as a plant conservation tool within Caribbean SIDS, using Trinidad as a case study. Prior to the application of SDM, ancillary analyses including: (i) quantification and mapping of forest cover change (1969 to 2007) and deforestation rates, and (ii) assessment of the island’s vegetation community distribution and associated drivers were carried out. Community distribution and commercial importance and global/regional rarity were used to generate a list of species for assessing the potential of SDM within Trinidad. Species occurrence data were used to generate species distribution models for present climate conditions within the SDM algorithm, MaxEnt. These results were assessed through expert appraisal and concurrence with results of ecological analyses. These models were used to forecast suitable species climate space forty years into an SRES A2 future. Present and future models were then combined to produce a ‘collective change map’ which showed projected areas of species’ range expansion, contraction or stability for this group of species with respect to Trinidad’s Protected Areas (PAs) network. Despite the models being indicative rather than accurate, it was concluded that species’ climate space is likely to decrease or disappear across Trinidad. Extended beyond Trinidad into the remainder of the Caribbean region, SDM may be a crucial tool in identifying which PAs within the region (and not individual islands) will facilitate future survival of given target species. Consideration of species conservation from a regional, rather than an individual island perspective, is strongly recommended for aiding the Caribbean SIDS to adapt in response to climate change.